Computed Tomography and Magnetic Resonance Imaging Features of Gracilis Myopathy in Dogs - Gunovska, Hana; Llanos, Cesar; Fitzgerald, Ella; Alcoverro, Emili; Flatz, Katharina; Gomes, César; Gomes, Sergio A. (Veterinary and Comparative Orthopaedics and Traumatology, 2024)
Objectives Gracilis myopathy is a well-recognized syndrome of weight-bearing gait abnormality; however, detailed description of computed tomography (CT) and magnetic resonance imaging (MRI) features of gracilis myopathy is lacking in the literature. This study aims to describe in detail CT and MRI features of gracilis myopathy.Study design This is a retrospective study. Medical records of dogs with characteristic gait and available pelvic limb MRI or CT, presenting to four referral institutions, were reviewed.Results Seven cases with MRI (3/7) or CT (4/7) were included, all German Shepherd dogs. MRI findings in all cases included a well-defined, T1-/T2-/proton density-weighted hypointense band along the axial margin of the gracilis muscle, shorter affected muscles, thickening and T2W/STIR hyperintensity with contrast enhancement at the symphyseal tendon, and concurrent focal indentation of the axial border of the gracilis muscle. CT findings included a hyperattenuating band (4/4), single instances of contrast enhancement at the origin of the muscle, thickening of the tendon at the origin and insertion, and concurrent thickening at the musculotendinous muscle.Conclusion CT and MRI can present advantages in correctly identifying the specific muscles affected within the gracilis–semitendinosus muscle complex. Both modalities can localize anatomically lesions in detail, for instance at the origin or insertion of the muscle, which could present advantages in novel treatment strategies for this condition.
Keywords: musculotendinous; contracture; thigh; lameness; semitendinosus